Multiresidue Method of Analysis of Pesticides in Medical Cannabis. (23rd November 2019) - Moulins, Jonathan R; Blais, Michel; Montsion, Kim; Tully, Josee; Mohan, William; Gagnon, Mathieu; McRitchie, Tyler; Kwong, Keri; Snider, Neil; Blais, David R
Abstract: Three related analytical methods were developed and validated for the determination of pesticides in cannabis leaves, dried cannabis flowers, and cannabis oil. The methods follow the generic sequence of an acetonitrile extraction, followed by solid-phase extraction cleanup and analysis by HPLC-tandem mass spectrometry (HPLC-MS/MS), GC-MS/MS, and GC-MS. These methods were developed to accommodate sample quantity and lipid content of the different matrices. Validation at a spiking level of 0.01 μg/g was successful for 39 pesticides in cannabis leaves and 40 pesticides in cannabis oil, and at 0.02 μg/g for 32 pesticides in cannabis flowers, with the majority of analytes showing recoveries within the acceptable range of 70–130%. With these methods established, unannounced inspections of Canadian licensed producers of cannabis revealed that out of 144 samples collected, 26 showed the presence of unauthorized pest control products.